Cannabidiol (CBD) for the treatment of subcutaneous treprostinil (Remodulin®) site pain: a case report - Brewer, Jacqueline; Kimber, Amy (Frontiers in Medicine, 2023)
Background Pulmonary arterial hypertension occurs as a result of vascular remodeling and dysregulation of endothelial cells that narrows small pulmonary arteries and raises precapillary pressures. Pulmonary arterial hypertension is a rare and progressive disease characterized by dyspnea, chest pain, and syncope. Parenteral treprostinil is indicated for the treatment of pulmonary arterial hypertension to diminish symptoms associated with exercise. Up to 92% of patients treated with treprostinil via subcutaneous delivery experienced infusion site pain and approximately 23% discontinued treatment due to site pain. Cannabidiol salve may have analgesic and anti-inflammatory properties and could be an additional option for patients with infusion site pain. Case report Two patients with pulmonary arterial hypertension were treated with cannabidiol salve. Both patients reported a reduction in infusion site pain without the need for narcotics. Conclusion These two cases suggest that cannabidiol salve may help to minimize redness and alleviate pain at the infusion site. Additional studies are required to test the effectiveness of cannabidiol in a larger group of patients with infusion site pain.